A case report Space Occupying Lesion - Pamarta, Alma Abigail; Fitriyani, Fitriyani; Putri, Giska Tri (CV. Jasa Sukses Abadi, 2025)
Space Occupied Lession (SOL) is a substantial physical lesion, such as neoplasm, bleeding, or granuloma located in the skull cavity. The most common causes of increased intracranial pressure in neurological cases are brain trauma, brain tumors, inflammation, and hydrocephalus. Mrs. SU, 46 years old, 17 November 2023 MRS with complaints of sudden unconsciousness since this morning, approximately 15 hours SMRS. Initially the patient complained of a severe headache accompanied by nausea and vomiting. The patient has a history of headaches for many years that have become worse for the past 3 days. To overcome headaches, patients often take paracetamol. Additional complaints: left eyelid closes and swells and cannot see at all. The patient had never previously experienced decreased consciousness. When he arrived, the patient's general condition appeared to be moderately ill with somnolence with a GCS of 9 (E2 V2 M5). Blood pressure 145/95 mmHg. After observation the next day, awareness of apathy with GCS 13 (E3 V4 M5). Blood pressure was 132/85 mmHg, on physical examination there was left ptosis and left eyelid edema. On visual acuity examination, the visual acuity was 3/60 and the left oculi was 1/. The pupil is round, anisocoric, with a central position. Nystagmus in the left oculi is positive. From the supporting examination, namely a CT scan, it was found that there was an amorphous isodense lesion with ill-defined boundaries in the left frontotemporal lobe measuring 6.5 cm x 5.4 cm with minimal perifocal edema, suspected of glioma, which deviated from the midline to the right as far as 0.5. cm. The patient's clinical diagnosis was increased intracranial pressure in the frontotemporal with the etiology of SOL caused by hydrocephalus. Management for this patient is medical treatment, namely: IV FD NaCl 0.9% 20 gtt/minute, Dexametson 1 ampoule/8 hours, Mannitol 250cc – 125cc – 75cc – 50 cc, Paracetamol 500 mg 3x1, Ceftriaxon 1 gr/12 hours, B12 2x1. VP-Shunt installation. For patients with a diagnosis of increased intracranial pressure caused by SOL and hydrocephalus, medical management and VP-Shunt installation will result in a good prognosis.